The role of information in the gender gap in the market for top managers: Evidence from a quasi‐experiment - Tsolmon, Ulya (Strategic Management Journal, 2024)
Abstract Research Summary This study examines the role of information in the gender gap in the executive labor market from the market frictions perspective. I ask whether increases in objective and reliable information about managerial quality close the gender gap in career advancements. To obtain exogenous variation in the availability of information, I exploit a natural experiment provided by the adoption of the International Financial Reporting Standards (IFRS) in 2005 by the European Union countries. I find that when reliable and objective information is more available, women executives are more likely to be hired away with promotion than men, especially from high‐performing firms. However, the gains in advancement rates are dampened in regions where societal views on women in the workplace are less favorable. Managerial Summary Bridging opportunity gaps for underrepresented groups remains a significant challenge for firms and policymakers. This research investigates the role of transparent financial disclosures by firms in closing the gender gap in executive promotions. Utilizing the adoption of the IFRS in EU countries, the study finds that women executives are more likely to be hired away with promotion than men, especially from high‐performing firms. However, less favorable societal views about working women weaken these effects. The study suggests that firms can leverage informational asymmetry in the labor market to access high‐quality managerial resources. Concurrently, firms must be cognizant of how financial regulations may affect their competitive edge in the executive talent market and adjust their internal retention policies accordingly.